2006
DOI: 10.1111/j.1365-2621.2005.01100.x
|View full text |Cite
|
Sign up to set email alerts
|

Compositional and physical properties of yogurts manufactured from milk and whey cheese concentrated by ultrafiltration

Abstract: Yogurts made with 80% milk retentate (MR) [Volume Reduction Factor (VRF) ¼ 1.5] and 20% cheese whey retentate (WR; VRF ¼ 8.0) (yogurt 1) and yogurts made with 100% MR through ultrafiltration have been evaluated as to flow, texture profile analysis (TPA) and syneresis index. As with MR and WR, their physico-chemical composition was also determined. The yogurt to which WR had been added showed; less apparent viscosity and greater tixotrophya; less firmness and adhesiveness and greater cohesiveness; higher synere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
29
0
8

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 49 publications
7
29
0
8
Order By: Relevance
“…Hardness and adhesiveness has increased with the addition of 1%, 2% and 3% RYRF to yoghurt during the storage period. These results agree with those obtained by the previous works who reported an increase in hardness and adhesiveness of yogurts obtained with the 2% oatmaltodextrin during refrigerated storage for 21 days [36,37], and those obtained by Kasenkas [38] during storage of probiotic torba yogurt. The adhesiveness had a positive effect on the thickness of the yogurts, and was an important factor governing the stability of the products resulting in good mouth-feel and improving the texture characteristics and the stability of yogurts during storage [38].…”
Section: Textural Propertiessupporting
confidence: 83%
“…Hardness and adhesiveness has increased with the addition of 1%, 2% and 3% RYRF to yoghurt during the storage period. These results agree with those obtained by the previous works who reported an increase in hardness and adhesiveness of yogurts obtained with the 2% oatmaltodextrin during refrigerated storage for 21 days [36,37], and those obtained by Kasenkas [38] during storage of probiotic torba yogurt. The adhesiveness had a positive effect on the thickness of the yogurts, and was an important factor governing the stability of the products resulting in good mouth-feel and improving the texture characteristics and the stability of yogurts during storage [38].…”
Section: Textural Propertiessupporting
confidence: 83%
“…10-13. Depicted data, which are consistent with values reported in other studies (1,(40)(41)(42)(43), reveal a low viscosity and a signifi cant syneresis of the product yielded at the highest temperature (t 3 =48 °C), as well as a low production and a pronounced syneresis of the yoghurt obtained at the highest clay/milk ratio (R 3 =7.5 g/L). Moreover, a grainy structure of the yoghurt samples was observed at the highest levels of t and R. Taking into account these aspects along with the heating and clay expenses, it can be concluded that the fermentation at the highest temperature and clay/milk ratio is unfavourable.…”
Section: Yoghurt Characterizationsupporting
confidence: 80%
“…Através do modelo da lei da potência, é possível avaliar se um fluido é pseudoplástico ou dilatante verificando-se o índice do comportamento de fluxo, que é menor do que 1 para fluidos pseudoplásticos e maior do que 1 para fluidos dilatantes (MAGENIS et al, 2006 …”
Section: Os Microrganismos Probióticos Da Espécieunclassified
“…Através do modelo da lei da potência, é possível avaliar se um fluido é pseudoplástico ou dilatante verificando-se o índice do comportamento de fluxo, que é menor do que 1 para fluidos pseudoplásticos e maior do que 1 para fluidos dilatantes (MAGENIS et al, 2006). Este parâmetro é fundamental no dimensionamento de equipamentos em indústrias de alimentos (BUFFO e REINECCIUS, 2002;CHUAH et al, 2007), sendo frequente A influência do uso de soro de queijo e bactérias probióticas nas propriedades de bebidas lácteas fermentadas CUNHA, T.…”
Section: Os Microrganismos Probióticos Da Espécieunclassified